Modern diagnostic X-ray sources : technology, manufacturing, reliability - Behling, Rolf (CRC Press, Taylor & Francis Group, 2021)
"Now fully updated the second edition of Modern Diagnostic X-ray Sources: Technology, Manufacturing, Reliability gives an up-to-date summary of X-ray source design for applications in modern diagnostic medical imaging. It lays a sound groundwork for education and advanced training in the physics of X-ray production, X-ray interactions with matter, imaging modalities, and assesses their prospects. The book begins with a historical overview of X-ray tube and generator development, including key achievements leading up to the current technological and economic state of the field"--